ЭВОЛЮЦИЯ ИДЕИ «СМЕРТЬ АВТОРА» (Filološke studije, 2019)
The authors describe the evolution of ideas about the «death of the author», starting from the theory of V. von Humboldt. Initially the main opposition in the philosophy was the opposition of the mind and matter (the subject and the object). After Humboldt in the classical dichotomy «thinking – reality» was introduced the third component is the language. Today, the main opposition is the opposition of the author and interpreter of (thinking) to the text (language) or even the «shell-text». The main object of philosophical studies – text, not the world.